Referral indications for foetal echocardiography in a low resource setting - Asma Ladak; Zahra Hoodbhoy; Shazia Mohsin; Salima Ashiqali; Saima Malik; Admin (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: The aim of this study was to review the primary indications for foetal echocardiography among pregnant women at a tertiary care center in a low resource setting. Methods: A retrospective record review was conducted of all women who have had a foetal echocardiogram between January 2015 and December 2016 at The Aga Khan University Hospital, Karachi, Pakistan. Information regarding maternal clinical characteristics, anomaly scan findings, indications for echocardiography, and findings on foetal echocardiogram was collected. Results: The dataset included 1909 patients. Maternal comorbidities including maternal diabetes, (n=614, 47%) was the most common maternal indications while multiple pregnancy (n=232, 38%) and intra-cardiac echogenic foci (n=168, 28%) was the most common foetal indication for referral. Major CHD was detected in 4.2% (n=81) of cases. In those with CHD, the most common indication for getting a FE was an abnormal 4-chamber (n=31, 38%) view on the screening obstetric ultrasound. Conclusions: Most of our patients were referred on the basis of indications that were not warranted based on international guidelines and very few had major CHD on FE. This emphasizes the need for justifying referrals for a resource intensive procedure such as FE. Keywords: Foetal echocardiography, congenital heart disease, low-resource setting, indications